PENGEMBANGAN MEDIA PEMBELAJARAN METODE ANFIS DI JURUSAN TEKNIK ELEKTRO UM - Nurus Sihab Aminudin; Anik Nur Handayani; M. Rodhi Faiz (SENTIA 2016, 2016)
Intelligent System is compulsary subject for students in Electrical Engineering Department, State University of Malang (TE, FT, UM). Undergraduated Students of Electronic Engineering Teaching (S1 PTE) and Students of Electronic Engineering (S1 TE) in Control System Skill. This lecture teaches the knowledge of artificial intelligence.Based on the lecturer’s interview result of Intelligent System lesson, there is no learning media which helps the learning process in ANFIS (adaptive neuro fuzzy inference system) material. It impacts the students understanding in material. According to the problem, the problem solving is that making a learning media for ANFIS. The media are module, simulation and jobsheet for ANFIS material.This research and development procedure is from ADDIE research and development model. ADDIE research procedures are: (1) Observing the need of the product in Intelligent System, (2) Desaigning the learning media in ANFIS method, (3) Developing module, simulation and jobsheet to reach one of the learning goal in Intelligent System, (4) Implementing the development learning media in ANFIS lesson which are validating and trying out, (5) Evaluating the learning media.The results of this learning media that was developed and validated by expert of content is 86.29%, expert of media is 92.18%, for small group is 91.11% and large group is 88.98%. The results of the validation, small group and large group explain that learning media in ANFIS method is feasible, so it can be used as a medium to assist the learning process in Intelligence System.